2019
DOI: 10.1080/21691401.2019.1615931
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein activates HSCs via hedgehog signalling during liver fibrosis development

Abstract: Recently, we showed that parathyroid hormone-like hormone (PTHLH), a cytokine-like polyprotein, is critical for extracellular matrix (ECM) deposition through the activation of hepatic stellate cells (HSCs).Here, we show that N-terminal PTHLH is secreted into the supernatant of injured hepatocytes, its expression is positively correlated with liver fibrosis severity based on mice liver biopsies, and it is primarily expressed in the cytoplasm of hepatocytes along the fibrous septa of fibrotic livers. PTHLH overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…PTH binds to PTH1R and activates the downstream signaling pathway to exert its function ( 40 ). Previous studies and our results proved that PTH1R is constitutively expressed in hepatic cells ( 12 , 38 , 39 ). We found that the inhibitory effect of PTH on PA-induced lipid accumulation was abolished by PTH1R knockdown in Hepa1-6 cells, demonstrating a direct and PTH1R-dependent effect of PTH on hepatocytes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PTH binds to PTH1R and activates the downstream signaling pathway to exert its function ( 40 ). Previous studies and our results proved that PTH1R is constitutively expressed in hepatic cells ( 12 , 38 , 39 ). We found that the inhibitory effect of PTH on PA-induced lipid accumulation was abolished by PTH1R knockdown in Hepa1-6 cells, demonstrating a direct and PTH1R-dependent effect of PTH on hepatocytes.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have evidenced the hepatic expression of Pth1r ( 38 , 39 ), the canonical G protein-coupled receptor for PTH and parathyroid-hormone-related protein (PTHrP) ( 40 ). To prove that PTH1R mediated the effects of PTH on lipid accumulation in hepatocytes, we transfected Hepa1-6 cells with Pth1r targeted siRNA or siRNA control and then induced intracellular lipid accumulation in Hepa1-6 cells by PA in the presence of PTH.…”
Section: Resultsmentioning
confidence: 99%
“…The dysfunction of probiotics has been confirmed as a major cause of multiple diseases. In this study, Bifico was fed to the mice, and we observed that it could decrease (31,32). It seems that the aberrant level of miR-34a is related to probiotic imbalance, although more evidence is necessary to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…A promising therapeutic strategy is to revert activated HSCs to a quiescent state. Although rottlerin was originally identified as an inhibitor of protein kinase C delta (PKCδ) (Gschwendt et al, 1994;He et al, 2019) and a recent report has shown that a general PKC inhibitor reduces a-SMA production in LPS-induced liver injury models in mice (Lee et al, 2013), a more detailed study has identified that rottlerin was an ineffective inhibitor of PKCδ activity, at least at micromolar concentrations (Soltoff, 2007). Systemically applied rottlerin was indicated to effectively treat experimental asthma via BK channel activation but without any effect on the control healthy mice (Goldklang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%